A Hipersexualização da Mulher Negra no Brasil através das Narrativas de Mulheres Negras de Araguaína-TO. - Costa, Ma Isabela Isaias da Rocha da (Universidade Federal do Tocantins, 2024)
The aim of this article is to seek to understand hypersexualization through the narratives of black women in the city of Araguaína-To, more precisely the students of the History course at the Federal University of Norte do Tocantins-Campus Cimba regarding the ways in which this cultural phenomenon presents itself and affects these women's lives. Referencing the discussion, hypersexualization, gender, identity and memory, this work was based on documentary and oral sources, also aiming at contributing to the Regional history of Tocantins by investigating this problem, which is the hypersexualization of black women through those who are most faced with her throughout her life.